Enzymatic synthesis of betulinic acid ester - Chew, Won Yin (2001)
Enzymatic synthesis of betulinic acid ester (3-β-hydroxyl-oley-lup-20(29)-en- 28-oic acid) from betulinic acid and oleic acid in chloroform were investigated. Five commercial lipases (Candida rugosa. Aspergillus niger. Penicillium roquerti. Novozyme 435 and Lipozyme) were tested for their suitability for the reaction. Among the lipase tested, Novozyme 435 and Lipozyme were chosen for optimization studies because of their higher specific activity. The effect of various reaction parameters such as time course, temperature, organic s01vent, amount of enzyme, mole ratio of substrates, initial water activity (aw) and continuous water activity (a,,) were studied to detennine optimal condition ofbetulinic acid ester. The optimal condition for betulinic acid ester synthesis using Novozyme 435 were obtained at incubation period of 13 h; temperature, 40˚C; mole ratio of substrates, 6.0; amount of lipase, 120 mg; organic solvent, chloroform, initial water activity (aw), 0.12 and continuous water activity (aw), 0.59. Optimal condition using Lipozyme were obtained at incubation period of 13 h; temperature, 50GC; mole ratio of substrates, 5.0; amount of lipase, 80 mg; organic solvent, chloroform; initial water activity (aw), 0.75 and continuous water activity (aw), 0.59. The maximum conversion for Novozyme 435 and Lipozyme at optimal condition were 95.15% and 64.55% respectively without removal of water in the reaction medium. This result clearly demonstrated that Novozyme 435 was well suited for the preparation of betulinic acid ester in organic media (chloroform). For scale up reaction, betulinic acid ester was easily isolated and purified using column chromatography with solvent system; anhydrous ether: hexane (20:8.0, v/v). The percentage conversion obtained was 75.68% when the reaction was scale up to thirteen folds. This study indicated that enzymatic reaction might be easily scaled up while maintaining the process selectivity as well as produced high yield of betulinic acid ester.